2020
DOI: 10.1088/1748-9326/ab6b35
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture is the main driver of deforestation in Tanzania

Abstract: Reducing deforestation can generate multiple economic, social and ecological benefits by safeguarding the climate and other ecosystem services provided by forests. Understanding the relative contribution of different drivers of deforestation is needed to guide policies seeking to maintain natural forest cover. We assessed 119 randomly selected plots from areas deforested between 2010 and 2017, in Tanzania. Through ground surveys and stakeholder interviews we assessed the proximate deforestation drivers at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…While in the case of developing countries like Africa, deforestation is continued for subsistence agriculture farming and wood production for local markets [43,44]. Agriculture and charcoal production are the main causes of deforestation in Tanzania [45] and fuel-wood in Senegal [46]. In Turkey, the main causes of deforestation are rapid urbanization and industrialization [47].…”
Section: Introductionmentioning
confidence: 99%
“…While in the case of developing countries like Africa, deforestation is continued for subsistence agriculture farming and wood production for local markets [43,44]. Agriculture and charcoal production are the main causes of deforestation in Tanzania [45] and fuel-wood in Senegal [46]. In Turkey, the main causes of deforestation are rapid urbanization and industrialization [47].…”
Section: Introductionmentioning
confidence: 99%
“…About 55% of Tanzania’s land area is occupied by woodlands and forests, and these areas are under increasing pressure from anthropogenic activities, especially agriculture 2 . The expansion of land areas for crops and grazing are the two largest causes of deforestation in the country 3 . The country has committed to reduce emissions by 10–20% relative to the business as usual scenario by 2030 under the Paris Agreement 4 , although to date, the agricultural sector is not included in Tanzania’s nationally determined contribution (NDC).…”
Section: Introductionmentioning
confidence: 99%
“…This is despite the evidence by authors such as Carter et al [67] on the role of crop and grazing land (including for livestock), as a driver of deforestation throughout sub-Saharan Africa. Further, recent studies speci cally in Tanzania [3] , have found that grazing land expansion itself is the 2 nd largest driver of deforestation, second only to cropland expansion. Based on the results of this study, feeding e ciency gains in the dairy sector are more likely to reduce emissions via avoided LUC rather than their impact on enteric fermentation or manure.…”
Section: Discussionmentioning
confidence: 98%